Review of the Management of Peroral Extrusion of Ventriculoperitoneal Shunt Catheter - Ghritlaharey, Rajendra Kumar (J Clin Diagn Res, 2016)
INTRODUCTION: Peroral extrusion of peritoneal part of Ventriculoperitoneal Shunt (VPS) catheter is an extremely rare complication following VPS implantation. AIM: To review the options available for the management of peroral extrusion of VPS catheter. MATERIALS AND METHODS: PubMed, Medline, PMC (PubMed Central), Embase, Google scholar databases search was performed to retrieve the published/available data relating to the peroral extrusion of VPS catheter. The keywords employed were “peroral extrusion of ventriculoperitoneal shunt catheter”, “transoral extrusion of ventriculoperitoneal shunt catheter”, and “oral extrusion of ventriculoperitoneal shunt catheter”. The maiden description of peroral extrusion of VPS catheter was reported in the year 1987, and the data relating to peroral extrusion of VPS were retrieved from that period to June 30, 2016, and those were available in English literature. RESULTS: Twenty-two published manuscripts (n) were available on the topic relating to peroral extrusion of VPS catheter. All were cases and were included for the review. This review included n=10; 45.45% male and n=12; 54.54% female. All of them were reported in children below 12-year of the age, except two case reports in adult that occurred at the age of 27-year and 47-year, respectively. Overall, the mean age at the time of peroral extrusion of VPS catheter was 6.94 ± 10.87 years. The interval from VPS insertion or last shunt revision to the occurrence of peroral extrusion of VPS catheter ranged from 10-days to 10-year, with a mean of 20.31 ± 28.37 months. More than two-third (n=15; 68.18%) of the case occurred within one-year of VPS insertion/last shunt revision. Clinical diagnosis was obvious in all the cases due to peroral extrusion of VPS catheter. The site of perforation by the VPS catheter was stomach in 15, jejunum in 1, diaphragm/trachea in 1, while the site of bowel perforation was not mentioned in 5 cases. Surgical procedures opted by authors in order of frequency were: (a) removal of entire VPS catheter n=5; (b) removal of entire VPS catheter, and delayed re-VPS n=5; (c) removal of peritoneal catheter with or without External Ventricular Drainage (EVD), and revision of peritoneal catheter n=3; (d) removal of peritoneal catheter, with or without EVD, and VA shunt n=3; (e) removal of peritoneal catheter, EVD and delayed re-VPS n=2; (f) removal of entire VPS catheter, EVD and delayed re-VPS n=2; (g) removal of peritoneal catheter, EVD and others n=2. Two deaths are also reported during the management of peroral extrusion of VPS catheter. CONCLUSION: Peroral extrusion of peritoneal part of VPS catheter is an extremely rare complication following VPS insertion, and most frequently observed in children, although also reported in adults. In more than two-third of the cases it occurred within one-year of the VPS placement or last shunts revision, so a close follow-up is a must during this period following VPS placement. Management of such a case depends upon many factors such as presence or absence of shunt tract infection, peritonitis, meningitis, and cerebro spinal fluid infection.